Frequent Flooding and Perceived Adaptive Capacity of Subarctic Kashechewan First Nation, Canada - Khalafzai, Muhammad-Arshad K.; McGee, Tara K.; Parlee, Brenda (ARCTIC, 2020)
Perceived (socio-cognitive) capacity is as important as objective (material resources) capacity in assessingthe overall adaptive capacity of people at the community level. Higher perceived and objective capacities generate greater total adaptive capacity. This article assesses the perceived adaptive capacity of the Kashechewan First Nation, located in the flood-prone southwestern James Bay (Subarctic) region in Canada. The community is frequently disrupted by the elevated risk of spring flooding and has experienced five major floods since its establishment in 1957. Residents have been evacuated 14 times since 2004 because of actual flooding or flooding risk and potential dike failure. We surveyed 90 residents using 21 indicators to assess the community’s perceived adaptive capacity. The results indicate that residents’ risk perception and perceived adaptive capacity are high and are reshaping their adaptive behavior to the hazard of spring flooding. The strong positive interrelationships between human capital, social capital, governance, and other determinants, such as migration, personal resilience, and experience, also suggest high perceived adaptive capacity. Human capital and the other determinants are relatively higher contributors to the perceived adaptive capacity, followed by social capital and governance determinants. The results also indicate that residents’ disaster preparedness has also improved. The elevated flooding risk and frequently occurring emergencies have motivated the First Nation to modify their spontaneous and proactive adaptation responses for disaster risk reduction at the individual, household, and band levels. Planning to adapt to natural hazards to mitigate their impacts also requires a nuanced understanding of the perceived adaptive capacity that contributes to overall adaptive capacity. Translating the high perceived adaptive capacity into greater total adaptive capacity would contribute to enhancing communityresilience. La capacité perçue (sociocognitive) est tout aussi ...